Recent evidence for direct oral anticoagulants in chronic kidney disease. Issue 3 (May 2019) - Ha, Jeffrey T.; Badve, Sunil V.; Jun, Min
Abstract : Purpose of review: The direct oral anticoagulants (DOACs) have emerged as an effective and safe alternative to vitamin K antagonists (VKAs) for stroke and venous thromboembolism (VTE) prevention. However, patients with chronic kidney disease (CKD) experience an increase in the risk of both thromboembolism and bleeding, and the risk–benefit profile of DOACs, particularly in advanced CKD remains a source of ongoing debate. This review summarizes the recent evidence on the effects of DOACs in CKD across a range of clinical indications including newly emerging indications. Recent findings: Data on early-to-moderate stage CKD derived from pivotal randomized controlled trials in broader atrial fibrillation and VTE populations support the favorable risk–benefit ratio of DOACs compared with VKAs in patients in these groups. However, safety data from observational studies comparing DOACs with VKAs in patients with atrial fibrillation and CKD (moderate to advanced) have been conflicting. Recent trials have evaluated the efficacy of low-dose DOACs on major cardiovascular outcomes, showing promising risk–benefit ratios in high-risk populations with concurrent CKD. Summary: Current data on patients with CKD derived from trials in the broader population suggest that DOACs are an effective alternative to VKAs in patients with early-to-moderate stage CKD. However, studies on patients with advanced CKD are lacking. Further randomized controlled trials, particularly those evaluating the risk of any clinically relevant bleeding as part of a more accurate assessment of the risk–benefit profile of DOACs in people with CKD, are needed.